(untitled) (Revista Argentina de Musicología, 2026)
This article examines the imaginaries of nature in Chilean political songs produced between 1966 and 1973, with a particular focus on the Popular Unity period. Through an analysis of lyrics, recordings and paraphonographic elements, two coexisting environmental imaginaries are identified in the discography of the Chilean left: one productivist, rooted in classical Marxism, which conceived of nature as a reserve of resources at the service of the revolutionary project; and another that explored alternative ways of relating to the more-than-human world, based on interdependence, care and learning. Through imagery such as the earth, animals, plants and elements of the natural environment, these songs constructed a symbolic universe which, without being presented as a rupture, gradually blurred the boundaries between the human and the non-human. Editorial History: Received: March 30, 2026 Accepted: July 8, 2026